The effect of individual cultural values and phantasy on risky investment intention - Aren, Selim; Nayman Hamamci, Hatice (EMERALD GROUP PUBLISHING LTD, 2023)
Purpose This study aims to examine the impact of conscious and unconscious processes on risky investment intention. In this framework, the effect of individual cultural values and phantasy on risky investment intentions was investigated. In addition, the mediating role of phantasy in the relationship between individual cultural values and risky investment intentions was also analyzed. Design/methodology/approach Data were collected between May 14, 2020 and June 01, 2020, when our graduate students voluntarily shared the online survey link on their social networks. In this way, 1,934 people in total answered the questionnaire. To test the study model, structural equation modeling (SEM) was performed using the AMOS program. In addition, ANOVA and independent sample t-test analyses were conducted using the SPSS program to analyze whether individual cultural values and risky investment intent differ according to demographic variables. Findings According to the analysis results, power distance, collectivism, masculinity and long-term orientation are seen as antecedents of phantasy. While a positive relationship was found between power distance, collectivism and risky investment intention, a negative relationship was found between uncertainty avoidance and risky investment intention. Statistical findings regarding the mediating effect of phantasy on the relationship between individual cultural values and risky investment intentions were also determined. In addition to these, the differences in individual cultural values and risky investment intentions according to age, education level, sex and marital status were investigated. Individuals with the highest uncertainty avoidance level were in the 41-50 age group. Individuals with the highest long-term orientation level were individuals aged 41 and over. Individuals with the lowest risky investment intentions were in the +51 age group. Collectivism and power distance did not differ according to age. There were no differences in the relevant variables according to the level of education. Males have higher levels of risky investment intention, power distance, masculinity and collectivism than females, and married individuals have higher levels of uncertainty avoidance, masculinity and collectivism than singles. Originality/value This study is the first to investigate the impact of conscious and unconscious processes on risky investment intentions together. On the other hand, the number of studies empirically investigating the relationship between phantasy and risky investment intention is quite limited, and the authors have also provided the findings for the existence of a relationship between these two variables.
Keywords: Individual cultural values; Phantasy; Risky investment intention; Power distance; Collectivism; Masculinity; Long-term orientation; Uncertainty avoidance; NATIONAL CULTURE; ENTREPRENEURIAL ORIENTATION; PHANTASTIC OBJECTS; COUNTRY; FINANCE; IMPACT; Business & Economics